An Empirical Analysis on the Sharing Economy: The Case of Airbnb in Warsaw - Kristof Gyodi (Institute of Economic Research (IER), 2017)
Research background: Consumption habits and the provision of services have undergone significant changes in the recent years. Platforms made way for new business models, which are often referred to as sharing economy or collaborative economy. Among the most valuable firms of the sharing economy is Airbnb, a platform for short-term accommodation rentals. Purpose of the article:The aim of the article is to analyse the characteristics of the Airbnb network in Warsaw, Poland. The paper investigates to what extent Airbnb may generate value from underused assets and whether it brings tourism todistricts previously less popular among visitors. Methodology/methods:The analysis is based on a unique dataset, which contains all Airbnb listings of Warsaw. The dataset has been constructed by the author using web-scraping technology. Descriptive statistics and kernel density estimation are implemented for the empirical analysis. Findings & Value added: The vast majority of the Airbnb network is focused on the short-term rental of entire homes and apartments in the city centre. Furthermore, the majority of listings belong to hosts, who offer more than one accommodation. The characteristics of the network suggest that the potential of Airbnb to generate value from underused assets is restricted: the primary activity of Airbnb decreases the number of properties on the long-term housing market. Comparing to traditional hotels, Airbnb is not significantly facilitating tourism in the outer districts of the city. The main contribution of the paper to the literature is the analysis of the entire population of Airbnb in a major city and the comparison with the traditional services sector. This is also the empirical analysis on the sharing economy and Airbnb in Poland.
Keywords: R12; D23; C81; 330; sharing economy; two-sided markets; digital economy; tourism